2009
DOI: 10.1093/jnci/djn441
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Use and Risk of Uveal Melanoma: Results of the Risk Factors for Uveal Melanoma Case-Control Study

Abstract: We recently reported an increased risk of uveal melanoma among mobile phone users. Here, we present the results of a case–control study that assessed the association between mobile phone use and risk of uveal melanoma. We recruited 459 uveal melanoma case patients at the University of Duisburg-Essen and matched 455 case patients with 827 population control subjects, 133 with 180 ophthalmologist control subjects, and 187 with 187 sibling control subjects. We used a questionnaire to assess mobile phone use and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
2
20
0
4
Order By: Relevance
“…However, this finding was not confirmed in a recent update of this German case–control study 10. As we have discussed in a previous publication, classification of exposure to RF emitting sources may be extremely difficult if based on personal reports of appliance use 26.…”
Section: Discussionmentioning
confidence: 62%
“…However, this finding was not confirmed in a recent update of this German case–control study 10. As we have discussed in a previous publication, classification of exposure to RF emitting sources may be extremely difficult if based on personal reports of appliance use 26.…”
Section: Discussionmentioning
confidence: 62%
“…[19][20][21] In brief, we conducted an incident case-control study at the University Hospital of Essen, the referral centre for eye tumors in Germany. The centre is located in North Rhine-Westphalia, the most populous Federal State in Germany.…”
Section: Cases and Controlsmentioning
confidence: 99%
“…The authors could not corroborate their previous results that showed an increased risk of uveal melanoma among regular mobile phone users. They accepted that probabilistic multiple error sensitivity analyses to evaluate the potential of exposure misclassification bias and selection bias did not explain the null result [61,62].…”
Section: Clinical Studiesmentioning
confidence: 99%